Factors Affecting Employees Motivation in Banking Sector of Pakistan - Akhtar, Naeem; Aziz, Shahzad; Hussain, Zahid; Ali, Saqib; Salman, Muhammad (Journal of Asian Business Strategy, 2014)
The aim of this study is to find out the relationship between the different factors (financial rewards, personal traits, high salary plans, job design and supervision) and employees motivation. In present study financial rewards, high salary plans, job design, personal traits and supervision are the independent variables and employee’s motivation is dependent variable. It is the quantitative research. For the data collection, study used the questionnaire method and data collection concerned with the banking sector of the Pakistan. In this paper study specified the sample size of 150 employees of the different banks in Pakistan. For the analysis of the data used the multiple regressions in this study. All the different variables have the positive impact on employee’s motivation. They contribute positively towards the employee’s motivation. This study conducted with the reference of Pakistan. It concluded that these factors have positive effect on employee’s motivation.